Bacterial Contamination and Antibiotic Resistance Patterns on POS and ATM Surfaces in Ahmadu Bello University, Zaria (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
The widespread use of Point of Sale (POS) systems and Automated Teller Machines (ATMs) has raised documented concerns about bacterial contamination and antibiotic resistance. This study investigated bacterial contamination, diversity, and antibiotic resistance profiles of isolates from ATM and POS surfaces at Ahmadu Bello University, Zaria. A total of 40 swab samples (20 from POS terminals and 20 from ATMs) were collected and analyzed using standard microbiological techniques. Results indicated that POS and ATM surfaces were contaminated with pathogenic bacteria, including Staphylococcus aureus and Escherichia coli. Enumeration revealed significantly higher total aerobic mesophilic counts on ATMs (6.94 x 10^5 CFU/mL) compared to POS (3.41 x 10^5 CFU/mL; P-value = 0.000); ATMs also had higher mean total Staphylococcal counts (TSE) and mean total coliform counts (TCE) than POS. The antibiotic susceptibility patterns showed that S. aureus isolates from ATMs were 100% susceptible to ciprofloxacin and tetracycline, and 50% susceptible to trimethoprim, gentamicin, and chloramphenicol, while showing 100% resistance to Amoxicillin and 25% resistance to chloramphenicol. Similarly, POS isolates showed 100% susceptibility to ciprofloxacin, 75% susceptibility to trimethoprim, chloramphenicol, and tetracycline, and 25% susceptibility to gentamicin. E. coli isolates from ATMs demonstrated 100% susceptibility to ciprofloxacin and tetracycline, and 75% susceptibility to trimethoprim, gentamicin, and chloramphenicol, with 100% resistance to Amoxicillin and 50% resistance to cefoxitin. Comparative analysis highlighted distinct differences in bacterial contamination, diversity, and antibiotic resistance between POS and ATM surfaces. Given these findings, implementation of routine disinfection protocols and public awareness initiatives is crucial to mitigate the risks of bacterial transmission and promote public health.
Keywords: Automated Teller Machine; Point of Sale machine; Staphylococcus aureus; Escherichia coli; Zaria